If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=6-11y+8y
We move all terms to the left:
9-(6-11y+8y)=0
We add all the numbers together, and all the variables
-(-3y+6)+9=0
We get rid of parentheses
3y-6+9=0
We add all the numbers together, and all the variables
3y+3=0
We move all terms containing y to the left, all other terms to the right
3y=-3
y=-3/3
y=-1
| -5f=-4-6f | | 5.99+1.99x=7.99+1.49x | | 9=6-11y+89 | | 5x+7=8x-9-5x | | 2/3(x-7)=12 | | 4(g+4)=2020 | | -21-4x+6x=11 | | -17-2x=-6x | | 2(3a-7)=13 | | 5n+2n=92 | | 5x+8=6(x+4) | | 7(1-3x)=9x-53 | | 9x-15=6x-12 | | v−–22=88 | | 7s-19-10s=13+s | | 5d-8=4+7d | | 3v−2=7 | | 9a−7a=3a−33+2a | | –3c+11c=–16 | | 24=v+14 | | -7y+7=24y-4 | | 2x+7−5x+8=3(5+6x)−12x= | | 50=40a | | 5/6x+21=1/6x+17 | | 6(3-x)=6 | | 4x+12-6x=16 | | -9-9-5f=-8f+9 | | -2x-(1/2)=1/4 | | -180=-8k-5(4K+8) | | 2(z-8)=2 | | -7(-3-x)=-2(2-x) | | -6(b+3)+6b=6b=-6(-4b+3) |